Open+: Versioning Open Social Scholarship - Arbuckle, Alyssa (KULA, 2019)
Advocates of the Open Access (OA) movement have been fighting for free and unfettered access to research output since the early 1990s. Open access is a crucial element of a fair, efficient scholarly communication system where all are able to find, interpret, and use the results of publicly-funded research. Universal open access is more possible now than ever before, thanks to networked technologies and the development of open scholarship policies. But what happens after access to research is provided? In this paper I argue that versioning scholarship across varying modes and formats would move scholarly communication from a straightforward open access system to a more engaging environment for multiple communities.